Efektivitas Mirror Therapy terhadap Peningkatan Kekuatan Otot pada Pasien Stroke: Kajian Literatur - Tamba, Daud Halomoan; Iswoyo, Grace Vika; Koanak, Yohana Diana; Watania, Lani Natalia; Fangidae, Erniyati (Universitas Malahayati, 2023)
ABSTRACT Stroke or Cerebrovascular disease is a disease caused by impaired brain function related to rupture or blockage of blood vessels that supply blood to the brain. Every year there are 13.7 million new cases of stroke and around 5.5 million deaths due to stroke. In Indonesia, it is estimated that around 2,129,326 people > 15 years have a stroke. Clinical manifestations that are often experienced by stroke patients are hemiparesis and hemiplegia so medical rehabilitation is needed. Mirror therapy is one of the non-pharmacological therapies that uses mirrors as a therapeutic medium. This literature review aims to describe the effectiveness of mirror therapy in increasing muscle strength in stroke patients. The method used was Thematic analysis: a simplified approach, with article searches using three databases namely Google Scholar, Medline, and JSTOR. Quality analysis of research methods has been carried out using PRISMA Flow Diagram and JBI Critical Appraisal Checklist. The keywords used in the article search were